Evaluation of the Paduka Website’s Performance in Improving Public Services at the Cirebon Regency Department of Population and Civil Registration - Nazua Nurul Rifani; Rd. Mahendra Haryo Bharoto (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
This research is motivated by the improvement of public services through digitalization at the Cirebon Regency Population and Civil Registration Office (DIDUKCAPIL) through the PADUKA website. The problem is that PADUKA ‘s performance is not fully optimal, as seen from the uneven distribution of service access between villages, the limited number of operators, and technical distruptions from the system or center that affect the speed of the application process. This study aims to evaluate the performance of the PADUKA website in improving public services, identify challenges faced, and assess public satisfaction with the quality and accessibility of PADUKA services. The method used is qualitative research with data collection techniques through observation, interviews, and documentation. Data analysis was carried out thematically based on six dimensions of performance evaluation, namely effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results of the study show that PADUKA services are easier for residents and help save time and costs compared to manual services. However, equal access remains a challenge. PADUKA needs to be continuously maintained and improved through socialization, adding operators, improving technical infrastructure, and increasing response in handling distruptions so that services run more consistently.